Artificial Multi‐Enzyme Networks for the Asymmetric Amination of sec‐Alcohols. Issue 12 (22nd January 2013) - Tauber, Katharina; Fuchs, Michael; Sattler, Johann H.; Pitzer, Julia; Pressnitz, Desiree; Koszelewski, Dominik; Faber, Kurt; Pfeffer, Jan; Haas, Thomas; Kroutil, Wolfgang
Abstract Various artificial network designs that involve biocatalysts were tested for the asymmetric amination of sec‐alcohols to the corresponding α‐chiral primary amines. The artificial systems tested involved three to five redox enzymes and were exemplary of a range of different sec‐alcohol substrates. Alcohols were oxidised to the corresponding ketone by an alcohol dehydrogenase. The ketones were subsequently aminated by employing a ω‐transaminase. Of special interest were redox‐neutral designs in which the hydride abstracted in the oxidation step was reused in the amination step of the cascade. Under optimised conditions up to 91 % conversion of an alcohol to the amine was achieved.